Vom Nutzen des Nichtwissens: Sozial- und kulturwissenschaftliche Perspektiven - Wehling, Peter (transcript, 2015)
Ignorance, inexperience, and above all the conscious lack of desire to know are still considered objectionable in today's »knowledge societies«. Not knowing is understood as a lack of supposedly indispensable knowledge to be remedied urgently. In contrast to this, the contributions to the volume contrast present diverse benefits of ignorance in different social contexts from the perspective of various disciplines - without denying its drawbacks.They show how active ignorance protects us from information overload, incriminating knowledge, and false certainty, but also how it can strategically be used to one's advantage.